Kinesiophobia, limits of stability, and functional balance assessment in geriatric patients with chronic low back pain and osteoporosis: a comprehensive study - Alshahrani, Mastour Saeed; Reddy, Ravi Shankar (Frontiers in Neurology, 2024)
This study aimed to examine LOS and functional balance in the geriatric population concurrently experiencing Chronic Low Back Pain (CLBP) and osteoporosis, in comparison to age-matched healthy controls; to assess the correlations between Kinesiophobia, LOS, and functional balance assessments; and to evaluate the mediating influence of Kinesiophobia on the association between LOS and functional balance tests.This cross-sectional study included a total of 86 participants in each group. Kinesiophobia was assessed using the Tampa Scale of Kinesiophobia (TSK). LOS variables were evaluated with a computerized Iso-free platform in eight different directions. Functional balance was measured using the Timed Up and Go (TUG) test and the Berg Balance Scale (BBS).Result: Patients with CLBP and osteoporosis showed significantly lower LOS percentages (45.78 ± 6.92) and impaired Functional Balance, reflected in a TUG Score (10.45 ± 2.23), compared to asymptomatic controls (LOS: 76.95 ± 8.21; TUG: 8.73 ± 1.90). Kinesiophobia showed a significant moderate negative correlation with LOS, indicated by r = -0.362 (p < 0.01). Additionally, Kinesiophobia was found to correlate with functional balance tests. Specifically, there was a moderate positive correlation with the TUG Score (r = 0.322, p < 0.01), indicating that higher Kinesiophobia is associated with slower TUG performance. Conversely, a moderate negative correlation was observed with the Berg Balance Scale (BBS) Score (r = -0.436, p < 0.001), suggesting that increased Kinesiophobia is associated with lower BBS scores, indicating poorer balance performance. Mediation analysis revealed that Kinesiophobia significantly influences LOS and Functional Balance. The findings emphasize the clinical relevance of addressing Kinesiophobia as a potential target for interventions aimed at improving LOS and functional balance in this specific patient population.